The Influence of production costs and sales volume on operational profit at Serasi Gorden Pringsewu: Case Study In Serasi Gorden’s Business In Pringsewu - Vivi Imelda; Sunarmi (Enrichment : Journal of Management, 2023)
This type of research uses quantitative research with a case study and field study approach. The data used is secondary data. The population in this study are all sales reports, production cost reports, and financial reports for Serasi Gorden's business. The samples used in this study were sales reports, production cost reports, and financial reports for the Serasi Gorden business for the period 2018 to 2022, namely 60 samples from 60 months for 5 years. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that production costs have a value of tcount <ttable or -38.034 <1.67065 with a significance value of 0.000 <0.05. Meanwhile, the sales volume variable has a tcount > ttable or 53.630 > 1.67065 with a significance value of 0.000 <0.05. So it can be concluded that partially production costs (X1) have no significant effect on increasing profits while sales volume (X2) has a significant effect on operating profits. From the simultaneous test of production costs and sales volume simultaneously, they have a positive and significant effect on Serasi Gorden's operating profit in Pringsewu with fcount > Ftable, namely 1567.144 > 3.15 and a significance of 0.000 <0.05 and the test results for the coefficient of determination is 98.2% , while the rest is influenced by other factors outside the two variables studied.